Skin aging: Neuroendocrine challenge - Mara Carsote; Florica Sandru; Simona Elena Albu; Mihai Cristian Dumitrascu; Eugenia Petrova; Ana Valea (Romanian Medical Journal, 2020)
Introduction. Skin is deeply affected by aging as all the organs do, including endocrine glands and neuroendocrine circuits. The anomalies of aging are connected to the internal aspects including hormonal panel mostly vitamin D status and glucocorticoid axes integrity, melatonin networking, thyroid function, and catecholamines/serotonin release), state of health/illness, genetic background and bio-neuroendocrine/neurotransmitters pathways as well as immune defence. Moreover, external environment elements like sun exposure, radiations, pollution, physical, chemical and biological agents are consistent with internal mentioned aspects. Our purpose is to provide a mini-review regarding neuroendocrine and endocrine perspective of skin aging. Particular aspects on glucocorticoids, vitamin D and 5-hydroxytryptamine are pointed out. This is a narrative type of review. Skin is situated at the crossroad between intrinsic and extrinsic aging and the neuroendocrine approach is essential for understanding its time dependent changes.